The golem's eye - Stroud, Jonathan (Stroud, Jonathan. Bartimaeus trilogy, 2005)
In their continuing adventures, magician's apprentice Nathaniel, now fourteen years old, and the djinni Bartimaeus travel to Prague to locate the source of a golem's power before it destroys London.